PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS MELALUI KEPUASAN SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PEMBELI TAHU BAXO IBU PUDJI UNGARAN) - Osell Anidya Ayu Aldiona; Handoyo Djoko Waloejo (Universitas Diponegoro, 2018)
Tahu bakso is a culinary made from tofu and processed beef or chicken from Ungaran. Tahu bakso Ibu Pudji is the first and the famous one who sells tahu bakso in Ungaran. This research is motivated by decreased sales target from Tahu Baxo Ibu Pudji. The purpose of this study aims to determine the influence of price and product quality as x variable to loyalty as y variable trough satisficationas z variable.The type of this research is an explanatory research, used non-probability sampling to 100 samples which were consumer of Tahu Baxo Ibu Pudji used purposive sampling and accidental sampling. This research used simple regression, and multiple regression as analysis methods, using t test as a hypothesis instrument and Sobel Test as mediator instrument. This research used SPSS Version 16.0 as measuring tools. The result shows that price has positive influential of 0,167 to satisfication with t test 2,119. Product quality has positive influential of 0,144 to satisfication with t test 3,629. Price and product quality has positive influential of 0,145 and 0,137 to satisfication with f test 8,637. Satisfication has positive influential of 0,752 to loyalty with t test 12,419. Price has positive influential of 0,245 to loyalty with t test 3,333. Product quality has positive influential of 0,155 to loyalty with t test 4,150. Price and product quality has positive influential of 0,222 and 0,145 to loyalty with f test 14,651. By the result of Sobel Test obtained between price to loyalty trough satisfication is 2,074 sum y p-value is 0.03800632. Between quality product to loyalty trough satisfication is 1,674 sum y p-value is 0,09406403. Between quality product to loyalty trough satisfication is 1,674 sum y p-value is 0,09406403. The writer suggest that the company should continue to provide a more affordable price and improve the product quality, so that the customer will continue to become a loyal customer. Tahu Baxo Ibu Pudji should continue to deliver satisfication to its customer.